2021
DOI: 10.1111/jorc.12378
|View full text |Cite
|
Sign up to set email alerts
|

Protein energy wasting and long‐term outcomes in nondialysis dependent chronic kidney disease

Abstract: Background: Nutritional status and protein energy wasting (PEW) is prevalent in patients with nondialysis-dependent chronic kidney disease (CKD). The relationship between PEW and long-term development of clinically important outcomes remains to be examined. Objectives:To investigate the relationships between PEW, as measured by Subjective Global Assessment (SGA 1-7), and progression to important clinical outcomes: mortality and/or kidney failure.Design: Prospective cohort design.Participants: One hundred and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Patients with CKD and undernutrition had a 2.4 times higher risk of infectious complications, lengthier hospital stay, and increased hospitalisation costs compared to those who were well-nourished [28]. Among adults with CKD, nutritional status assessed through SGNA was associated with kidney failure, mortality, poor physical function and gastrointestinal symptoms [29,30]. In adults on maintenance hemodialysis, individual measures of PEW, such as low BMI, hypoalbuminemia, and normalized protein catabolic rate, have been shown to be associated with infection-related mortality [31].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD and undernutrition had a 2.4 times higher risk of infectious complications, lengthier hospital stay, and increased hospitalisation costs compared to those who were well-nourished [28]. Among adults with CKD, nutritional status assessed through SGNA was associated with kidney failure, mortality, poor physical function and gastrointestinal symptoms [29,30]. In adults on maintenance hemodialysis, individual measures of PEW, such as low BMI, hypoalbuminemia, and normalized protein catabolic rate, have been shown to be associated with infection-related mortality [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the subgroup analysis, we found that, among patients with a CKD, an NRS 2002score ≥ 3 points was associated with a higher risk for in-hospital mortality. In patients with CKD, protein-energy wasting is common [37] and is associated with disease progression and mortality [38]. A recent study described an association of an NRS 2002-score ≥ 3 with in-hospital mortality also in hospitalized patients with CKD [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although factors associated with early mortality have not been fully studied, the majority of early death can be attributed to cardiovascular events or infections, and mortality is significantly higher among PEW patients ( 29 ). PEW may increase susceptibility to catheter-related infections and cardiovascular events related to hemodynamic stress during dialysis ( 30 ). Therefore, targeted nutritional interventions need to be best implemented in the early stage of dialysis.…”
Section: Discussionmentioning
confidence: 99%